PENGEMBANGAN EKONOMI LOKAL KOTA PALEMBANG MELALUI KAJIAN POTENSI KLASTER INDUSTRI KECIL - Mukhlis Mukhlis; Dirta Pratama A; Nabila Dehannisa (Jurnal Ekonomi Pembangunan, 2014)
Local economic development study of Palembang aims to identify types of small and medium industries that have the potential to be developed in the city of Palembang as well as the appropriate strategy for its development. The data used are secondary obtained from the Department of Industry, Trade and Cooperation of Palembang, the Central Bureau of Statistics and Bank Indonesia. The analytical tool used is Location Quotient (LQ) and Typology Klassen. Based on the calculation of LQ, there are four districts that have LQ value greater than 1 is the District Sukarami, Ilir Timur II, Gandus, and Small Hill. While the classification based on growth and contributions obtained: 1) small and medium industry of chemical and building materials sector has grown rapidly classification; 2) small and medium industry of clothing and leather sector has rapidly grown and fast classification advance; 3) small and medium industry of the metal sector and services; and general craft has quickly advanced classification but depressed; and 4) small and medium industry of food group has a relatively low classification. The strategy for the development of small and medium industries in the city of Palembang is through pembe¬rian facilities development, human resource development, equipment, and marketing assistance through pro¬mosi and exhibitions both at provincial and national levels Keywords: Small and Medium Enterprises, Economic Growth, Local Economy, Location Quotient, Typology Klassen.